Age and Spatial Peculiarities of Non-neoplastic Diseases of the Skin and Subcutaneous Tissue in Kazakhstan, 2003-2015 - Nurbek IGISSINOV; Dariyana KULMIRZAYEVA; Zarina BILYALOVA; Gulnur AKPOLATOVA; Marzya MAMYRBAYEVA; Galina ZHUMAGALIYEVA (Tehran University of Medical Sciences, 2017)
Background: Arrangement of effective management aimed at improving dermatological services and consistent care of patients with skin diseases depends on understanding the epidemiological situation. Methods: This retrospective study presents an epidemiological assessment of non-neoplastic skin and subcutaneous tissue diseases in Kazakhstan registered in 2003-2015. Results: The yearly incidence rate of the diseases among the whole population was in average 3,341.8±121.1per 100000 population. This represents 4835.0±156.1 for children, 5503.2±141.8 for adolescents and 2646.6±106.7for adults per 100000 inhabitants.Space and time incidence rate was evaluated according to the administrative division. The overall trend decreased to 3.5% in children to 2.8% in adolescents to 1.9%, and in adults to 3.9%. Considerable variation in rates was seen across the country, with highest rates in East Kazakhstan, Mangystau and Aktobe regions, the lowest - in Atyrau and South-Kazakhstan regions. Conclusion: Non-neoplastic diseases of skin and subcutaneous tissue continue to be an urgent public health problem, especially among children in many regions of Kazakhstan.